About the Legal Basis of Russian Citizens Visafree Travel on Cruise Ships to European Union Countries - Alexander M. Oreshenkov (Московский журнал международного права, 2014)
The article deals with the regulatory framework of entry of foreigners – passenger of cruise ships and ferries in to Russia and the EU, as well as problems of visa-free entry of passengers of Russian cruise ships in the EU member states that given the political will of the CEC could be solved by enforcing just EU laws and London Convention on Facilitation of International Maritime Traffic, or by concluding a bilateral agreement between Russia and the EU.